RNA Secondary Structurome Revealed Distinct Thermoregulation in Plasmodium falciparum - Qi, Yanwei; Zhang, Yuhong; Mu, Quankai; Zheng, Guixing; Zhang, Mengxin; Chen, Bingxia; Huang, Jun; Ma, Changling; Wang, Xinhua (Frontiers in Cell and Developmental Biology, 2022)
The development of Plasmodium parasite, a causative agent of malaria, request two host and the completion of 11 different parasite stages during development. Therefore, a quick and efficient response of parasites to various environmental changes, such as the temperature, pH, ion, and nutrient, is essential for the parasite development and survival. Among many of these environmental changes, it has been shown that the temperature is decisive factor for parasite development and pathogenesis, including the thermoregulation of the rRNA expression, gametogenesis and parasite sequestration in cerebral malaria. However, the exact mechanism of how plasmodium parasites rapidly respond and adapt to the temperature change remain elusive. RNA structure can as a pervasive and fundamental regulator of gene expression, which can be an extremely specific and subtle mechanism for fine tuning a variety of cellular processes. For example, the dynamic and temperature-dependent RNA structural changes are able to regulate gene expression program as shown for RNA thermometers. In this study, we apply the recent in vivo and in vitro genome-wide secondary structurome approach to measure the parasite RNA structure changes with the temperature alteration at single-nucleotide resolution for ring and trophozoite stage parasite. Among 3000 probed structure at different temperature, our data showed the structure change in the global transcriptome, such as s-type rRNA, HRPII gene, the erythrocyte membrane protein family. With the temperature dropping from 37°C to 26°C, the trophozoite stage genes alter RNA structure significantly than ring stage. Combined analysis of icSHAPE with transcriptome data reveals that stage specific RNA structure play an important role in regulation of the gene expression for parasite in response to the temperature change. In addition, we identified and verify several RNAT which responded quickly for temperature change. The possible thermos-responsive RNAs (motifs) in P. falciparum were further mapped. To this end, we identified dynamic and temperature-dependent RNA structural changes in the P. falciparum transcriptome and performed a comprehensive characterization of RNA secondary structures over the course of temperature-stress in blood-stage development. This finding not only contributes better understanding of function of RNA secondary structure but may also provide novel targets for efficient vaccine or drugs.